THE TOKUR GOLD DEPOSIT (FAR EAST, RUSSIA) - Eirish L.V.; Ostapenko N.S.; Moiseenko V.G. (My University, 2002)
The Tokur deposit explored to a depth of 400 m and distance of 3 km is well studied. The enclosing Middle-Upper Paleozoic(?) sandy-clay rocks forming the Chelogor anticline with a dome-shaped arch and of a latitudinal strike are slightly metamorphosed. The anticline is crossed by preore longitudinal and transverse faults and intruded by abundant postore Jurassic-Cretaceous porphyrite dikes of submeridional strike and younger (Cretaceous) quartz diorite stocks. Ore bodies are represented by quartz veins filling bed-conformable and oblique fractures. Veins are composed of quartz (90 vol %), calcite, sericite, and adularia. Ore minerals (1-4 vol %) are arsenopyrite and pyrite (main mass), galena, sphalerite, chalcopyrite, fahlore, and, at deeper levels, scheelite. Gold is fine to, sometimes, visible; its fineness ranges from 600 to 800, commonly, 700-750. Ore veins form vein zones. Ore shoots in ore bodies plunge at steep angles. Sometimes, they are distributed downward in an echelon manner. The main sulfide mineral is pyrite at upper levels and arsenopyrite (together with scheelite), lower. The gold fineness increases downward. The geochemical zoning is as follows: W-Zn-As-Pb-Ag-Au-Hg. The age of quartz-adularia hydrothermolites determined by the 40Ar-39Ar method in the Alaskan University, USA, is 113.5 Ma. The study of gas-liquid inclusions (GLI) implies that cations in preore fluids were mainly dominated by Ca, K, and, to a lesser extent, N and Mg, whereas anions were mainly represented by bicarbonate, S, and, less commonly, Cl. The productive stage was characterized by an elevated Na content. In postore fluids, Ca and Mg dominated with a subordinate amount of K and Na cations; anions were represented by bicarbonate. The low-temperature fields mark the main channels of prolonged infiltration of orebearing fluids at the productive stage and correspond to areas of maximum opening of the ore-localizing structure. Therefore, they are characterized by an elevated vein thickness. The results of the fluid inclusion study in native gold and measurements of the decrepitation temperature suggest the crystallization of gold at the temperature interval of 180-380°C.